Effectiveness of daptomycin against infective endocarditis caused by highly penicillin-resistant viridans group streptococci - Takahiro Matsuo; Nobuyoshi Mori; Aki Sakurai; Takayoshi Kanie; Yumiko Mikami; Yuki Uehara; Keiichi Furukawa (IDCases, 2021)
Penicillin-resistant viridans group streptococci (VGS) infections are an emerging issue in infectious diseases. Here, we present a case of mitral valve infective endocarditis caused by highly penicillin-resistant VGS (minimum inhibitory concentration >4 μg/mL), which was successfully treated with daptomycin. Although the clinical efficacy of daptomycin has not been established, it can be an alternative for the treatment of highly resistant VGS endocarditis.